Dipole polarizability of Sn 120 and nuclear energy density functionals - Hashimoto, T.; Krumbholz, A. M.; Reinhard, Paul-Gerhard; Tamii, A.; Von Neumann-Cosel, P.; Adachi, T.; Aoi, N.; Bertulani, C. A.; Fujita, H.; Fujita, Y.; Ganioʇlu, E.; Hatanaka, K.; et al. (Physical Review C - Nuclear Physics, 2015)
The electric dipole strength distribution in Sn120 between 5 and 22 MeV has been determined at the Research Center for Nuclear Physics, Osaka, from polarization transfer observables measured in proton inelastic scattering at E0=295 MeV and forward angles including 0°. Combined with photoabsorption data, a highly precise electric dipole polarizability αD(Sn120)=8.93(36)fm3 is extracted. The dipole polarizability as isovector observable par excellence carries direct information on nuclear symmetry energy and its density dependence. The correlation of the new value with the well-established αD(Pb208) serves as a test of its prediction by nuclear energy density functionals. Models based on modern Skyrme interactions describe the data fairly well while most calculations based on relativistic Hamiltonians cannot.
CRIS-Team Scopus Importer:2023-07-24